Optimal visual cryptographic scheme with multiple share creation for multimedia applications. Issue 78 (September 2018) - Geetha, P.; Jayanthi, V.S.; Jayanthi, A.N.
Highlights: An new approach to improve privacy and confidentiality for multimedia data-security. OGWO-based iterative process for the generation of optimal keys. Opposition base learning (OBL) process is used to enhance the conventional GWO. Detailed experimental result is analyzed with the existing approaches. Abstract: The criminal activity of hackers to retrieve the highly secured information on multimedia application generates major security concerned problems towards the human life. Basically, the visual cryptographic scheme generates numerous unreasonable image shares with specific information. The secret information hidden in the image can be retrieved by accumulating all the shares. The basic idea that relays on this cryptographic scheme is the encryption of image which hides the secret into m numerous image shares. By this process, it turns to be complex for the hackers to retrieve an original data of the image. Moreover, to increase the confidentiality and privacy of the original image there is in demand to make use of the efficient encryption algorithm. In this paper, the proposed visual cryptographic scheme is divided into three phases namely, (a) Separation of color bands, (b) Generation of numerous shares and (c) Optimal Encryption and Decryption. For optimal encryption and decryption of the image, we propose an OGWO based ECC (Elliptic Curve Cryptographic) approach. Initially, the input color image is separated into three color bands such as R, G and B. Subsequently, multiple image shares are generated based on the pixel measures. After this process, the shares of the image are partitioned into blocks and decrypt the original image using the optimal key generated by the OGWO (Oppositional Gray Wolf Optimization) algorithm. From the experimental analysis, we inferred that for the decrypted image PSNR achieved is 59.012, 0.11 for MSE and the CC is 1, without experiencing any deviations in the original image. Graphical abstract: